Income Level of Street Vendors in Meeting Family Economic Needs in Passo Village, Baguala District, Ambon City - Seleky, Neni Filian; Sihasale, Daniel Anthoni; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Street vendors _ is wrong one perpetrator or effort economy today 's democracy move in effort trading the informal sector which has many touched by policy government area . Destination study this that is for could know effect of length of business , level of income per day , as well how influence time selling to level income street vendor . _ Type research used _ that is which descriptive _ attempted for decide solving existing problem _ with use SWOT method use knowing Strength, Weakness, Opportunity and Threat. Results Study this showing that level income street vendors in the village Passo has Fulfill needs economy like education , clothing , board and food as well as the average health has 100% met.